Mt10-CVB3 Vaccine Virus Protects against CVB4 Infection by Inducing Cross-Reactive, Antigen-Specific Immune Responses - Ninaad Lasrado; Rajkumar Arumugam; Mahima T. Rasquinha; Meghna Sur; David Steffen; Jay Reddy (Microorganisms, 2021)
Group B coxsackieviruses (CVB) containing six serotypes, B1–B6, affect various organs, and multiple serotypes can induce similar diseases such as myocarditis and pancreatitis. Yet, no vaccines are currently available to prevent these infections. Translationally, the derivation of vaccines that offer protection against multiple serotypes is highly desired. In that direction, we recently reported the generation of an attenuated strain of CVB3, termed Mt10, which completely protects against both myocarditis and pancreatitis induced by the homologous wild-type CVB3 strain. Here, we report that the Mt10 vaccine can induce cross-protection against multiple CVB serotypes as demonstrated with CVB4. We note that the Mt10 vaccine could induce cross-reactive neutralizing antibodies (nABs) against both CVB1 and CVB4. In challenge studies with CVB4, the efficacy of the Mt10 vaccine was found to be 92%, as determined by histological evaluation of the heart and pancreas. Antibody responses induced in Mt10/CVB4 challenged animals indicated the persistence of cross-reactive nABs against CVB1, CVB3, and CVB4. Evaluation of antigen-specific immune responses revealed viral protein 1 (VP1)-reactive antibodies, predominantly IgG2a, IgG2b, IgG3, and IgG1. Similarly, by using major histocompatibility complex class II tetramers, we noted induction of VP1-specific CD4 T cells capable of producing multiple T cell cytokines, with interferon-γ being predominant. Finally, none of the vaccine recipients challenged with CVB4 revealed the presence of viral nucleic acid in the heart or pancreas. Taken together, our data suggest that the Mt10 vaccine can prevent infections caused by multiple CVB serotypes, paving the way for the development of monovalent CVB vaccines to prevent heart and pancreatic diseases of enteroviral origin.